Vegetative state outcomes improved over the last two decades. (23rd February 2018) - Aidinoff, Elena; Groswasser, Zeev; Bierman, Uri; Gelernter, Ilana; Catz, Amiram; Gur-Pollack, Rotem
ABSTRACT: Objective : To describe late outcomes in patients with prolonged unawareness, and factors affecting them. Design : A retrospective study of 154 patients with traumatic brain injury (TBI) and 52 with non-traumatic brain injury (NTBI), admitted for intensive care and consciousness rehabilitation (ICCR), in a vegetative state (VS) lasting over 1 month. Results : Survival rate (67% total) was higher than in past studies carried out at the same facility ( p < 0.01). Consciousness recovery rate (54% total) was higher in NTBI VS patients ( p < 0.01) than in earlier cohorts, and similar in TBI VS patients, despite their older age than that of earlier cohorts. No meaningful differences were found in characteristics or in outcomes between the TBI and NTBI groups. Age, length of stay in ICCR, and hydrocephalus were found to affect survival ( p < 0.001). Younger age, absence of hydrocephalus, and anti-Parkinsonian medication contributed to consciousness recovery after VS ( p < 0.05). Conclusions : The present study demonstrated an improvement in survival and recovery of consciousness in VS patients over the last two decades, and similar outcomes for both TBI and NTBI VS. Outcomes suggest that acute medical care and ICCR have contributed to advances in VS care.